Big Data with the importance of information sharing - Joshi, Suman Lata; Singh, Shivanshu (IJRDO -Journal of Computer Science Engineering, 2016)
Data comes from everywhere, sensors used to gather climate information, posts to social media sites, digital pictures and videos etc this data is known as big data. Useful data can be extracted from this big data with the help of data mining. With the fast development of networking, data storage, and the data collection capacity, Big Data is now rapidly expanding in all science and engineering domains, including physical, biological and bio-medical sciences. This paper provides an overview of big data mining and discusses the related challenges and the new opportunities. We address broad issues related to big data and/or big data mining, and point out opportunities and research topics as they shall duly flesh out. We hope our effort will help reshape the subject area of today’s data mining technology toward solving tomorrow’s bigger challenges emerging in accordance with big data.